Hypoxia‐induced cytosolic calcium influx is mediated primarily by the reverse mode of Na+/Ca2+ exchanger in smooth muscle cells of fetal small pulmonary arteries. Issue 6 (June 2014) - Sun, Yanjuan; Ye, Lincai; Liu, Jinfen; Hong, Haifa
Abstract Aim Constriction of small pulmonary arteries and high resistance of pulmonary circulation are important for maintaining fetal circulation before birth. In this study, we investigated how cytosolic free calcium concentration ([Ca2+]i) in fetal lamb small pulmonary artery smooth muscle cells (SPASMC) was affected by hypoxia and regulated by calcium pumps during this process. Methods (Ca2+)i in response to acute hypoxia was determined spectrofluorometrically with fluo‐3AM in cultured fetal SPASMC. Chemicals or solutions, including ryanodine, 2‐aminoethoxydiphenyl borate, Ca2+‐free solution with 20 mmol ethyleneglycoltetraacetic (EGTA), nimodipine, Na+‐free medium and KB‐R7943, were administrated at the same time point when samples were exposed to acute hypoxia. Results (Ca2+)i in fetal lamb SPASMC increased under acute hypoxia. 2‐Aminoethoxydiphenyl borate, an inhibitor of inositol triphosphate calcium store, partially attenuated the (Ca2+)i increase after 6‐min treatment. Ryanodine, an inhibitor of ryanodine‐sensitive calcium stores, had no effect on the (Ca2+)i increase. Ca2+‐free solution with EGTA completely abolished this increase. Both nimodipine, that blocks the voltage‐gated calcium channel, and KB‐R7943, that inhibits the reverse mode of Na+/Ca2+ exchanger, greatly diminished the hypoxia‐induced (Ca2+)i increase. The inhibitory effect of KB‐R7943 was stronger than nimodipine, evidenced by the fact that (Ca2+)i dropped near to the baseline level in the presence of KB‐R7943 at a later time point. Low extracellular Na+ concentration enhanced the hypoxia‐induced increase of (Ca2+)i. Conclusion These results suggest that hypoxia‐induced Ca2+ increase in fetal SPASMC results from cytosolic Ca2+ influx mediated primarily by the reverse mode of Na+/Ca2+ exchanger.